Performance analysis of reed-solomon coded fast frequency-hopped MFSK systems with multitone jamming and AWGN over fading channels - Xia, Wei (2008)
In this thesis, closed-form bit-error rate (BER) expressions for a Reed-Solomon (RS) coded fast frequency-hopped M-ary frequency-shift-keying (FFH/MFSK) linear-combining receiver over multitone jamming (MTJ) ad additive white Gaussian noise (AWGN) channels are derived based on the characteristic function approach.